Factors that influencing the improvement of employee performance in Oriental Melaka Straits Medical Centre / Shahida Lemat@Limat - Lemat@Limat, Shahida (Faculty of Business and Management, 2017)
There are major problems like low engagement, productivity and skillfulness occur among employees in Oriental Melaka Straits Medical Centre. These crises were deriving from several factors such as negative attitude and behavior, carelessness, discouragement and so on. The main objective of this study was to investigate the factor that influencing the improvement of employee performance in Oriental Melaka Straits Medical Centre (OMSMC). The study reviewed several theories of training and development, motivation and rewards as possible avenues towards a framework of understanding what factor influencing the improvement of employee performance. A convenience sampling technique was used to select a sample of 210 respondents from a target population of 400 employees. Questionnaires were used to collect primary data while secondary data was collected through document review. Data analysis was carried out using quantitative technique with the aid of Statistical Package for Social Science (SPSS) version 20 while figures, tables and charts were used for data presentation. The study found that from three independent variables assessed in the study, only two have shown a significant relationship which are the training and development and motivation with the improvement of employee performance while rewards not. Regarding the findings, it can be concluded that the respondents highly agreed that training and development and motivation influenced the improvement of their performance while rewards not.